The new era of whole-exome sequencing in congenital heart disease: brand-new insights into rare pathogenic variants - Pasipoularides, Ares (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
CHD is a complex developmental phenotype, with many genes contributing to its etiology; it affects about 1% of infants, and its genetic roots are multifarious and difficult to ascertain (1,2). Improvements in prenatal diagnosis, corrective procedures, and longitudinal support have reduced infantile mortality. Today, >75% of CHD children surviving beyond their 1st year, including those with complex malformations, will live into adulthood (3). Despite medical and surgical advances, CHD leads birth-defect mortality. Genetic factors have long been implicated, as children with genetic disorders are more prone to heart disease.